A finite element model of the Hydrodynamics around hydrofoils - Carbonel, C. A. A. (2015)
In this paper, a finite element model is presented to predict the hydrodynamics around hydrofoils. The proposed model solves the equations of conservation of mass and momentum, including advection, pressure and shear stress terms. To describe the influence of turbulence, the Prandtl- Kolmogorov model is considered. A transport equation is included in the formulation to simulate the evolution of water vapor fraction. Weakly reflective boundary conditions are imposed on open boundaries to avoid the intense reflections of the pressure waves that generate instability. Various numerical experiments are performed using the hydrodynamic profile NACA 0012. The non permanent model results reproduce the essential characteristics of the flows around the hidrofoils in various cases. The model is able to describe the mixture of liquid and vapor when the pressure is below the vapor pressure during cavitation phenomena.